Pharmaceutical interventions in patients using insulin analogues under judicial demand assisted at the Centro de Especialidades Médico Odontológica, in Belém, Pará (Research, Society and Development, 2021)
Objective: To present the pharmaceutical interventions offered to users using insulin analogues under judicial review, through pharmaceutical services available at the Centro de Especialidades Médico Odontológica, in Belém, Pará. Method: This is a prospective, descriptive, analytical study of a qualitative and quantitative nature, carried out in patients with Diabetes Mellitus in the age group between 50 and 59 years old, of both sexes and genders, using analogous insulins judicialization, through participatory observation, using convenience sampling carried out between August 2018 and June 2019. Results: 27 users, 15 female and 12 males, aged between 50 and 59 years, completed the 3 Pharmaceutical Consultations. 29.6% of users had some complication related to diabetes; among which, the prevalence of diabetic retinopathy at 50%. Casual capillary blood glucose decreased from 215.29 ± 80.56 mg / dL to 131 ± 34.74 mg / dL. Insulin glargine (Lantus®) was found in 94% of prescriptions. 85.2% self-reported having adhered to treatment. R $ 454.87 was the average monthly cost of treatment for users. 100.0% of users were classified as having a good quality of life. Conclusion: It is inferred that pharmaceutical interventions have been shown to be effective about pharmaceutical care and the quality of life of the user. It is proposed to reflect on the importance not only of accessibility to insulin analogues via the courts; but, fundamentally, the quality of access to the care services offered.